Nasa: Communication for Life. - ROZENTAL, EMMANUEL; ALMENDRA, VILMA (NACLA Report on the Americas)
The article reports on how the Nasa people have transformed the use of electronic media by placing it at the service of their communities. The Nasa were prompted to react against violence in their community after members of the Revolutionary Armed Forces of Colombia (FARC) launched a cylinder bomb into a hospital in the town of Toribío. The Nasa also decided to confront the military and the FARC, urging them to leave their community.